Design, synthesis and evaluation of pyrrolo[2, 3-d]pyrimidine-phenylamide hybrids as potent Janus kinase 2 inhibitors. Issue 12 (15th June 2016) - Wang, Tingfang; Liu, Xiaofei; Hao, Meixi; Qiao, Jianan; Ju, Caoyun; Xue, Lingjing; Zhang, Can
Graphical abstract: A series of novel pyrrolo[2, 3- d ]pyrimidine-phenylamide hybrids were designed using the hybridization strategy and synthesized as potential JAK2 inhibitors. Abstract: Janus kinase 2 (JAK2) plays an essential role in the signaling of hormone-like cytokines and growth factors, which has been convinced as an important target of myeloproliferative neoplasms (MPNs) therapy. In this study, a series of novel pyrrolo[2, 3- d ]pyrimidine-phenylamide hybrids were designed and synthesized as potential JAK2 inhibitors through hybridization strategy. In vitro biological studies showed that most of these compounds exhibited potent activity against JAK2. Especially, compound16c was identified as a suitable lead compound, which showed favorable pharmacokinetic profiles in rats ( F  = 73.57%), excellent in vitro efficacy against erythroleukemic cells (TF-1, IC50  = 0.14 μM), and high selectivity for JAK2 (IC50  = 6 nM with >97-fold selectivity vs JAK3).